PERAN KEPEMIMPINAN KIAI DALAM MENINGKATKAN MUTU PENDIDIKAN (STUDI KASUS DI PONDOK PESANTREN BAHRUL MAGHFIROH KOTA MALANG) - Syafi'i Syafi'i (STAI Ma'had Aly Al-Hikam Malang, 2019)
The leadership of the kiai becomes very important in Islamic boarding school because the development of the quality of pesantren education depends on the competence of the leader, the meaning of the leader here is the kiai or caretaker of the boarding school. This study aims to describe the first role of leadership in improving the quality of education, secondly the leadership of kiai that is effective in improving the quality of education in Islamic boarding schools.This research uses a qualitative method, with a case study in Bahrul Maghfiroh Islamic Boarding School in Malang. Data collection was carried out using interview, observation, and documentation and observation techniques. Data analysis uses descriptive qualitative methods and inductive thinking patterns. The purpose is to analyze the data obtained from field objects, and then to be related to relevant theories.The results showed: 1) The role of the kiai in improving quality in the Bahrul Maghfiroh Islamic boarding school in Malang is as a manager, educator, human resource empowerment, decision maker, attainee of the pesantren, motivator and supervisor. 2) Effective kiai leadership is leadership that builds cooperation with kiai or other institutions, regenerates kiai and builds good relations with the community.